Factors Affecting Treatment Adherence Among Patients with Tuberculosis in Indonesia: Literature Review - Fahrul Islam; Haeranah Ahmad; Nurbaya; Masnaeni Ahmad; Ansar; Kadar Ramadhan; Muhammad Syukri; Syafran Arrazy; Agung Aji Perdana; Deborah Siregar; Nining Ade Ningsih; Ikes Dwi Astuti; et al. (Journal of Public Health and Pharmacy)
Introduction: Tuberculosis (TB) is the leading cause of death from infectious diseases in the world and Indonesia is the second largest contributor to TB cases after India. Treatment adherence problems are a major obstacle to TB elimination. The purpose of this Literature Review is to determine the factors that affect treatment adherence among TB patients in Indonesia.